Ca2+/Calmodulin Complex Triggers CAMTA Transcriptional Machinery Under Stress in Plants: Signaling Cascade and Molecular Regulation - Iqbal, Zahra; Shariq Iqbal, Mohammed; Singh, Surendra Pratap; Buaboocha, Teerapong (Frontiers in Plant Science, 2020)
Calcium (Ca2+) ion is a critical ubiquitous intracellular second messenger molecule, acting as a lead currency for several distinct signal transduction pathways. Transient perturbations in free cytosolic Ca2+ ([Ca2+]cyt) concentrations are indispensable for the translation of signals into adaptive biological responses. The transient increase in [Ca2+]cyt levels is sensed by an array of Ca2+ sensor relay proteins such as Calmodulin (CaM), eventually leading to conformational changes and activation of CaM. CaM, in a Ca2+-dependent manner, regulates several transcription factors (TFs) that are implicated in various molecular, physiological, and biochemical functions in cells. CAMTA (Calmodulin-binding Transcription Activator) is one such member of the Ca2+-loaded CaM-dependent family of TFs. The present review focuses on Ca2+ as a second messenger, its interaction with CaM and Ca2+/CaM-mediated CAMTA transcriptional regulation in plants. The review recapitulates the molecular and physiological functions of CAMTA in model plants and various crops, confirming its probable involvement in stress signaling pathways and overall plant development. Studying Ca2+/CaM-mediated CAMTA TF will help in answering key questions concerning signaling cascades and molecular regulation under stress conditions and plant growth, thus improving our knowledge for crop improvement.